AB0104 Role of CD14+ and CD16+ Monocyte Subtypes in The Atherothrombosis Associated with Rheumatoid Arthritis: Epigenetic Mechanisms Involved. (15th July 2016) - Barbarroja, N.; Ruiz-Limon, P.; Perez-Sanchez, C.; Jimenez-Gomez, Y.; Abalos-Aguilera, M.C.; Arias de la Rosa, I.; Segui, P.; Font, P.; Aguirre, M.A.; Calvo, J.; Ortega, R.; Castro, M.C.; et al.
Abstract : Background: Monocytes play a key role in the pathogenesis of the cardiovascular disease (CVD). Three monocyte subsets have been described based on their CD14 and CD16 profile, with different actions in the vascular pathology. The distribution of these monocytes subsets and their epigenetic profile associated with CVD in rheumatoid arthritis (RA) remain unravelled Objectives: To functionally characterize the monocytes subsets in RA patients and analyze their role in the endothelial dysfunction, altered oxidative status and proinflammatory/prothrombotic profile associated to RA. Methods: Fifty RA patients and 30 healthy donors were included. Endothelial function was measured through post occlusive hyperaemia using Laser-Doppler. Carotid intima media thickness (CIMT) was used as atherosclerosis marker. The monocyte subsets were characterized by flow cytometry and isolated by immuno-magnetic selection. Proinflammatory cytokines, peroxides levels and cellular activation markers were analyzed. NanoString nCounter miRNA Expression Array was used to profile 800 microRNAs in isolated CD14+ and CD16+ monocytes. PCR array gene expression was used to analyze the expression of 84 genes related to atherosclerosis. Target genes of the differentially expressed miRNAs were identified by using the Ingenuity Pathway Analysis Software (IPA). The predicted microRNA-mRNA interactions were characterized by the microRNA Target Filter tool of IPA. The resulting identified interactions were revalidated by RT-PCR on the whole cohort of RA patients Results: CD16+ monocytes were significantly extended in RA patients. These subsets had increased protein and gene expression of proinflammatory cytokines, markers of atherosclerosis and peroxide levels. miRNA expression profiling showed that 38 miRNAs were significantly altered (≥2 fold) in CD14+ RA monocytes compared to CD16+ RA monocytes. Functional classification of those miRNAs showed a preponderance of targets mRNAs involved in the pathological process of RA such as inflammatory state, immune response and CVD. RA patients had impaired endothelial function, with a reduced perfusion value after ischemia. Increased CD16+ monocytes and reduced CD14+ cells percentage were associated with a pathologic CIMT. Clinical parameters strongly correlated with endothelial dysfunction, decreased percentage of CD14+ monocytes and increased number of CD16+ subsets. Conclusions: 1) RA patients exhibit an increased number of CD16+ monocytes, which display a specific atherogenic and inflammatory pattern directly associated to the autoimmune profile, the progression of the disease and the altered microvascular function. This atherogenic profile might be associated with an altered epigenetic pattern. That data suggest that CD16+ subpopulation might play a key role in the CVD pathogenesis associated with RA. Acknowledgement: Funded by CTS7940, PI15/01333, PI2013–0191, CP15/00158 Disclosure of Interest: None declared